The Treasured Things of Tokelau - Huntsman, Judith (Waka Kuaka, 2017)
Drawing upon multiple lines of research in and about Tokelau—ethnography as participant-observation and conversation/discussion, documentary research in all available published sources (few) and unpublished materials in offices and archives, Tokelau narratives and texts, conversations with other scholars of Tokelau, and relevant anthropological literature—the late Antony Hooper and I have aimed to create a narrative of Tokelau over time and in places that speaks to both differences and continuities in Tokelau lifeway—their activities and beliefs, ideas and relationships. This essay is a contribution to and illustration of our endeavours, focusing on those particular things that Tokelau people treasure: their emblematic resources and the valued things they make from them, and their supreme valued treasures—pearl-shells (tifa), and the lures (pā) and pendants (kahoa) fashioned from them.